Pengaruh Struktur Kepemilikan terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan Dimoderasi oleh Independensi Dewan Direksi - Putri Hana Khairunnisa; Anita Anita (Faculty of Economics, Universitas Internasional Batam, 2021)
The main focus of this study is to examine the interactions effect of ownership structure on corporate social responsibility disclosure and the moderating effect of board independence. The control variables used are profitability, firm size, firm age, leverage, and board size. A total of 451 companies are used and listed on the Indonesia Stock Exchange (IDX). The purposive sampling method is used in the company's annual report from 2015-2019 and is processed using Eviews. The findings obtained after testing the data show that foreign ownership has a positive and significant effect. The moderating effect of the board independence in this study affects the ownership structure (government, institutional, and foreign) on the disclosure of corporate social responsibility which is significantly positive.